2018
DOI: 10.26434/chemrxiv.5909833.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alkaline Earth Metal Oxide Nanocluster Modification of Rutile TiO2 (110) Promotes Water Activation and CO2 Chemisorption

Abstract: Metal oxide photocatalysts are widely studied for applications in solar driven environmental remediation, antimicrobial activity, hydrogen production and CO<sub>2</sub> reduction to fuels. Common requirements for each technology include absorption of visible light, reduced charge carrier recombination and the ability to activate the initial molecule be it a pollutant, water or CO<sub>2</sub>. The leading photocatalyst is some form of TiO<sub>2</sub>. A significant amount of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…The other adsorption modes in Figure 6 are of more interest, and these show new C−O interactions with the supported nanoclusters, and the adsorption structure is consistent with a carbonate-like adsorption mode, albeit without the strong stabilization usually found for carbonate adsorption, 64,65 and consistent with the CO 2 adsorption on the Bi-oxide-terminated pyrochlore. 44 Table 3 which is consistent with its larger adsorption energy and distortions away from the gas-phase CO 2 geometry.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The other adsorption modes in Figure 6 are of more interest, and these show new C−O interactions with the supported nanoclusters, and the adsorption structure is consistent with a carbonate-like adsorption mode, albeit without the strong stabilization usually found for carbonate adsorption, 64,65 and consistent with the CO 2 adsorption on the Bi-oxide-terminated pyrochlore. 44 Table 3 which is consistent with its larger adsorption energy and distortions away from the gas-phase CO 2 geometry.…”
Section: Resultssupporting
confidence: 56%
“…In our earlier work, the emphasis has been on new heterostructured materials with predicted visible light absorption 47−59 and reduced charge recombination. 48−52,60−62 We have recently studied the interaction of molecules, such as CO 2 , with tin(II) oxide, 47 zirconia, 47 manganese oxide, 63 alkaline earth oxide, 64 and ceria 65 nanocluster-modified TiO 2 heterostructures. We have found that such nanoclustermodified TiO 2 heterostructures can adsorb CO 2 , 47 but that some heterostructures, such as reduced MnO x −TiO 2 , do not show favorable CO 2 adsorption, even though reduced cations are present.…”
Section: Introductionmentioning
confidence: 99%